Effects of feeding rumen–protected amino acids on the performance of feedlot calves - Mazinani, Mitra; Naserian, Abbas Ali; Rude, Brian J; Tahmasbi, Abdol Mansour; Valizadeh, Reza (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was conducted to produce and evaluate protected amino acids (AAs) against degradation in the rumen with greater bioavalibility and without the problems associated with polymer coating and the effect this has on calf performance. Materials and Methods: In the first step, essential AAs methionine and lysine were reacted with two chemical compounds (Benzaldehyde and Glutaraldehyde) in an attempt to make ligands for producing protected AAs. The physico-chemical characterization, melting point, and mass spectrometric of products were estimated. These products were fed to 36 Holstein dairy calves with 110 ± 0.50 kg of average body weight and an age of 110 ± 10 days. Calves were randomly assigned to six treatments. This study was done with six treatments as a completely randomized one-way design. Results: Feed consumption and average daily gain were less for control animals and those fed methionine and lysine glutaraldehyde compared to other treatments. The largest chewing time was observed for methionine and lysine glutaraldehyde, respectively, and the least was control. There was no difference for energy consumption, dry matter intake, or blood metabolites among the six treatments. The greatest total protein content was related to methionine and lysine glutaraldehyde treatment and the least total protein was observed in control treatment. Conclusion: It can be concluded that the use of chemical methods to protect AAs can be applied and may have some beneficial effects. Adv. Vet. Anim. Res., 7(2): 229-233, June 2020